Bernyanyi untuk Belajar: Mengoptimalkan Pembelajaran Bahasa Indonesia dengan Metode Bernyanyi - Sudirman, Suryanti; Nursyamsi, Nursyamsi; Mirnawati, Mirnawati (South Sulawesi Education Development, 2025)
This research aims to find out: 1) a picture of learning readiness before using the singing method in Indonesian language learning, 2) a picture of learning readiness after using the singing method in Indonesian language learning 3) the influence of the singing method on learning readiness in Indonesian language learning. This research is a quasi-experiment research with a single-group interrupted time-series design approach. The location of this research was carried out at SDN 283 Mahalona, ​​Towuti District, East Luwu Regency. The population in this study were all class I students at SDN 283 Mahalona for the 2023/2024 academic year. Sampling was carried out using a total sampling technique with a sample size of 22 people. The research instrument used was a questionnaire and data analysis using the paired samples t test with a significance level of 5%. The results of the research show that 1) students' learning readiness before using the singing method in Indonesian language learning obtained high results, 2) students' learning readiness after using the singing method in Indonesian language learning obtained very high results, 3) there was an influence of the singing method on learning readiness in class I Indonesian language learning at SDN 283 Mahalona, ​​Towuti District, East Luwu Regency. Keywords: , ,